2010
DOI: 10.17221/94/2009-cjas
|View full text |Cite
|
Sign up to set email alerts
|

An association of C/T polymorphism in exon 2 of the bovine insulin-like growth factor 2 gene with meat production traits in Polish Holstein-Friesian cattle

Abstract: ABSTRACT:The effect of the insulin-like growth factor 2 (IGF2) gene polymorphism -a g.292C>T transition in exon 2 on feed uptake and conversion, growth rates, and meat production traits in Polish HolsteinFriesian cattle was investigated. A total of 291 young bulls were genotyped using restriction fragment length polymorphism (RFLP-BsrI). Animals were slaughtered at the age of 11 or 15 months and carcass traits were examined. At the age of 11 months the association was shown of the CC genotype with higher cold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 20 publications
2
11
1
1
Order By: Relevance
“…Compared with previous cattle research (Goodall and Schmutz, 2003;Zwierzchowski et al, 2010), the IGF-II gene appears to be highly conserved in yaks, and results indicated a very low mutation rate. It was previously reported that the g.292C>T transition in the IGF-II gene (RFLPBsrI) influenced meat production traits in Polish Holstein-Friesian bulls (Zwierzchowski et al, 2010). In a Canadian beef cattle herd, animals with the CT genotype had a significantly lower mean REA relative to those with the CC genotype, but a significantly higher REA than those with the TT genotype (Goodall and Schmutz, 2007).…”
Section: Discussioncontrasting
confidence: 65%
See 4 more Smart Citations
“…Compared with previous cattle research (Goodall and Schmutz, 2003;Zwierzchowski et al, 2010), the IGF-II gene appears to be highly conserved in yaks, and results indicated a very low mutation rate. It was previously reported that the g.292C>T transition in the IGF-II gene (RFLPBsrI) influenced meat production traits in Polish Holstein-Friesian bulls (Zwierzchowski et al, 2010). In a Canadian beef cattle herd, animals with the CT genotype had a significantly lower mean REA relative to those with the CC genotype, but a significantly higher REA than those with the TT genotype (Goodall and Schmutz, 2007).…”
Section: Discussioncontrasting
confidence: 65%
“…For most traits, the AA and BB genotypes appeared to be favorable, which is consistent with the activity of the IGF-II protein as a growth factor (Heude et al, 2007). However, the observed effects were relatively small, thus suggesting that the mutation is not the primary or causative agent for variation in the traits evaluated (Zwierzchowski et al, 2010). Compared with previous cattle research (Goodall and Schmutz, 2003;Zwierzchowski et al, 2010), the IGF-II gene appears to be highly conserved in yaks, and results indicated a very low mutation rate.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations